EVALUATION OF THE WORK PROGRAM IMPLEMENTATION OF THE STRATEGIC PLAN SENIOR HIGH SCHOOL OF STATE 28 KAB TANGERANG - Mulyanto, Agus Iwan (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2019)
This research is evaluating the Strategic Plan work program at Senior High School. Observational methods use CIPP (Context, Input, Process, Product) models by Stufflebeam & Shinkfield. This program is one type of object of evaluation research (Evaluation Research). The fundamental orientation in all evaluation research is benefits. The strategic plan for implementing the Senior High School program needs to mark improvements related to the MIA and IIS Study Programs. Suggested observations of implementers Strategic Plan followed up on many findings, especially those concerning the program, and make improvements to the program so that the Strategic Plan program process activities become more effective.Keywords: Strategic Plan, Work Program Evaluation.